Root Cause Analysis and Its Effect on Auditors' Judgments and Decisions in an Integrated Audit* - DeZoort, Todd; Doxey, Marcus; Pollard, Troy (Contemporary Accounting Research, 2021)
ABSTRACT This study evaluates whether auditor use of root cause analysis (RCA) for an identified client misstatement affects auditors' assessments of underlying control issues and materiality in an integrated audit setting. We also test whether auditor cognitive style moderates these effects given prior findings that a misfit between task structure and cognitive style undermines performance. This research is motivated by concerns about integrated audit quality and auditors failing to consider control deficiencies indicated by client misstatements. We randomly assigned 147 auditors to four RCA treatments (No RCA, Unstructured RCA, Structured “5 Whys” RCA, Structured “Fishbone” RCA). As predicted, the results suggest that auditors using (not using) structured RCA are more (less) likely to identify control‐related root causes of a financial misstatement and judge the misstatement to be more (less) material. Also consistent with our prediction, we find that the assessed severity of identified control deficiencies mediates RCA's effect on materiality judgments. Finally, the materiality judgment results reveal the expected significant interaction between structured RCA method and auditor cognitive style, suggesting the importance of allowing flexibility in the specific RCA method applied in practice. Overall, the study's results provide evidence that auditor use of RCA as a judgment framework prompts deeper evaluation of audit findings and stronger consideration of critical links between financial reporting and related internal controls in integrated audit settings.